Prevention of rabies in Southern Siberia - I. D. Zarva; A. D. Botvinkin (Фундаментальная и клиническая медицина)
Aim. To substantiate the need for coordinating measures to prevent rabies in adjacent territories with similar conditions for the spread of this infection.Materials and Methods. We retrospectively analyzed spatiotemporal trends in rabies spread during 1950-2020 by studying available statistics from nine Siberian territories (Altai Republic, Altai Region, Tyva Republic, Khakassia, Buryatia, Krasnoyarsk Region, Transbaikal Region, Irkutsk Region and Kemerovo Region). Mapping of rabies cases in humans (n = 124) and animals (n = 1648) was carried out using QGIS 3.16.3, ArcMap 10.8.1 and ArcScene 10.8.1 software and open electronic landscape maps Natural Earth and OpenStreetMap.Results. We revealed two periods of intensive rabies spread in southern Siberia: 1) from 1950 to 1983; 2) from 2002 to the present time. However, human rabies was recorded only during the first period. In all studied territories, inter-epizootic periods lasted from 10 to > 40 years. Geographical analysis identified a mosaic localization pattern and a relative isolation of the affected areas. After 2002, there has been a connection between location of animal rabies cases with agricultural lands and a consistent advance of epizootics from west to east and north-east in all territories, excepting Irkutsk Region. The identified regional features of the spatial distribution of rabies were due to a mountainous terrain and a connection of some forest-steppe areas with similar landscapes of neighboring countries.Conclusions. Southern Siberia is characterized by long rabies-free periods and by the infection foci isolated from other areas as a result of periodic viral invasions from adjacent territories. These features determine the common approaches to the organization of preventive measures across the territories, suggesting their increased efficiency due to the numerous natural barriers and the possibility to concentrate the resources within the small areas. Our results indicate the feasibility of a regional approach to rabies control.